Intraoperative elastography and spinal surgery: a systematic review of current and future applications in clinical and preclinical models - Dhillon, Parker; Saway, Brian Fabian; Galimba, Audrey; Suresh, Rishishankar; Eckert, Thomas; Kerensky, Max J.; Vattipally, Vikas N.; Kramer, Patrick; Theodore, Nicholas; Patel, Sunil; Kalhorn, Stephen (The Ultrasound Journal, 2025)
Background: While conventional imaging provides excellent structural detail of the spine, it cannot assess the mechanical properties of spinal tissue in real time. Ultrasound elastography (USE) is an emerging modality that quantifies tissue stiffness, offering a potential solution to this diagnostic gap. This review synthesizes the current evidence for the use of USE in spinal pathology.Main body: A systematic review of the PubMed, Cochrane, and Web of Science databases was conducted in accordance with PRISMA guidelines, yielding seven primary studies, three clinical and four preclinical, published between 2015 and 2024. These studies, comprising preclinical and clinical data, demonstrate USE's ability to provide real-time, quantitative feedback. Key applications identified include quantifying tension relief in tethered cord syndrome, differentiating spinal tumors from healthy tissue based on stiffness values, and assessing the biomechanical severity of acute and chronic spinal cord injury. Shear wave elastography (SWE) was the predominant modality, proving superior to strain elastography (SE) for spinal applications.Conclusion: USE is a powerful adjunct to traditional spinal imaging, providing unique functional data that can enhance intraoperative surgical precision and decision-making. While challenges such as depth penetration and operator standardization remain, continued research and technological innovation position USE to significantly improve diagnostic accuracy and surgical outcomes in spinal disease management.